The gut microbiota in experimental abdominal aortic aneurysm - Xiao, Jie; Wei, Zhanjie; Yang, Chuanlei; Dai, Shilin; Wang, Xiancan; Shang, Yuqiang (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: Abdominal aortic aneurysm (AAA) is a life-threatening disease and there are no effective treatments to inhibit aneurysm progression and rupture. The gut microbiota has been increasingly recognized, and is considered a new therapeutic target, because of its role in host homeostasis. However, the role of gut microbiota and abdominal aortic aneurysm has not been clarified. Therefore, we performed 16S rRNA analysis to determine and compare the composition of the gut microbiota between the AAA and Control groups. Methods: We used the classical angiotensin-II induced abdominal aortic aneurysm mice model to investigate the role of gut microbiota and abdominal aortic aneurysm. The mice were randomly assigned to 2 groups: the Control (n=7) group received saline (vehicle), while the AAA (n=13) group received solutions of Ang II. Aortic tissue and fecal samples were harvested after 28 days of infusion. Fecal samples were analyzed by 16S rRNA sequencing. Results: The levels of Oscillospira, Coprococcus, Faecalibacterium prausnitzii, Alistipes massiliensis, and Ruminococcus gnavus were increased in the AAA group, while those of Akkermansia muciniphila, Allobaculum, and Barnesiella intestinihominis were increased in the Control group. Furthermore, the network analysis and ZiPi score highlighted the phylum Bacteroidetes as the keystone species. PICRUSt2 analysis revealed that PWY-6629 (a super pathway of L-tryptophan biosynthesis), PWY-7446 (sulfoglycolysis), and PWY-6165 (chorismate biosynthesis II (archaea)) may-be involved in the metabolic pathways that contribute to AAA formation, and E.coli/Shigella may be the key bacteroid that influences those three pathways. Conclusion: Alterations in the gut microbiota may associated with the formation of AAA. Akkermansia and Lactobacillus were significantly decreased in the AAA group, but the keystone species Bacteroidetes and its metabolic products should be given more attention in AAA formation research.